A Coupled Groundwater–Surface Water Modeling Framework for Simulating Transition Zone Processes. Issue 3 (24th October 2016) - Mugunthan, Pradeep; Russell, Kevin T.; Gong, Binglei; Riley, Michael J.; Chin, Arthur; McDonald, Blair G.; Eastcott, Linda J.
Abstract: There is an identified need for fully representing groundwater–surface water transition zone (i.e., the sediment zone that connects groundwater and surface water) processes in modeling fate and transport of contaminants to assist with management of contaminated sediments. Most existing groundwater and surface water fate and transport models are not dynamically linked and do not consider transition zone processes such as bioturbation and deposition and erosion of sediments. An interface module is developed herein to holistically simulate the fate and transport by coupling two commonly used models, Environmental Fluid Dynamics Code (EFDC) and SEAWAT, to simulate surface water and groundwater hydrodynamics, while providing an enhanced representation of the processes in the transition zone. Transition zone and surface water contaminant processes were represented through an enhanced version of the EFDC model, AQFATE. AQFATE also includes SEDZLJ, a state‐of‐the‐science surface water sediment transport model. The modeling framework was tested on a published test problem and applied to evaluate field‐scale two‐ and three‐dimensional contaminant transport. The model accurately simulated concentrations of salinity from a published test case. For the field‐scale applications, the model showed excellent mass balance closure for the transition zone and provided accurate simulations of all transition zone processes represented in the modeling framework. The model predictions for the two‐dimensional field case were consistent with site‐specific observations of contaminant migration. This modeling framework represents advancement in the simulation of transition zone processes and can help inform risk assessment at sites where contaminant sources from upland areas have the potential to impact sediments and surface water. Abstract : Article Impact Statement : A new modeling tool for an enhanced representation of groundwater–surface water transition zone processes in contaminant fate and transport.